Effects of hyperglycemia and metformin on expression of adhesion molecules on human aortic endothelial cells - Bačun, Tatjana (Array, 2008)
Summary: Expression of adhesion molecules on the endothelial cell surface as a response to elevated glucose concentration is considered as a main event in the development of atherosclerosis. The influence of high glucose concentration and metformin, a wide used anti-diabetic drug, on the expression of E-selectin, vascular adhesion molecule-1 (VCAM-1) and intercellular adhesion molecule-1 (ICAM-1) on human aortic endothelial cells (HAECs) was investigated. HAECs were cultured 4 h in a medium with 5.5, 8.0, 12.0, and 16.5 mmol dm-3 glucose with or without metformin addition. The expression of cell adhesion molecules (CAM) was measured by flow-cytometry. Compared to CAM expression in the medium with 5.5 mmol dm-3 glucose, glucose concentration of 12.0 mmol dm-3 increased expression of E-selectin (62 %), VCAM-1 (four fold) and ICAM-1 (81 %). Metformin administration in the medium with 12.0 mmol dm-3 glucose additionally enhanced E-selectin and VCAM-1 expression compared to effects of corresponding glucose concentration. ICAM-1 expression was only significantly increased in the medium with metformin and 8.0 mmol dm-3 glucose. In conclusion, metformin in condition with elevated glucose concentration additionally increased expression of CAM on HAECs which could contribute to development of macrovascular complications in diabetic patients